A modular modeling approach for investigating wool critical buckling from biologically variable along-fiber microstructure. Issue 3 (February 2021) - Vetharaniam, Indrakumar; Plowman, Jeffrey E; Brorens, Peter; Harland, Duane
Mammalian hair fibers are internally sophisticated. We introduce a modeling approach aimed at use in research that derives value from understanding how microstructural organization generates effects at the macroscopic level in the context of natural biological variation. Critical buckling load is solved using a numerical approach applied to a modular fiber microstructure model where fibers of arbitrary length are made up of snippets composed of serial cross-sections at 25 micrometer intervals. As an example, the model is applied to investigate how much effect changes to single microstructural properties (fiber ellipticity, cortical cell type distribution and cell type proportion) have on critical buckling load in the context of prickle. Potential uses and key weak areas in our knowledge of wool fiber morphology and biophysics are discussed.